Dopamine agonist monotherapy utilization in patients with Parkinson’s disease - Monica Frazer; Steve Arcona; Lisa Le; Rahul Sasane (Clinical Parkinsonism & Related Disorders, 2023)
Objectives: To characterize patients with Parkinson’s disease (PD) who initiated dopamine agonist (DA) monotherapy, describe medication utilization and provider types, and estimate medication adherence and discontinuation rates. Methods: Retrospective study identified patients with PD in the Optum Research Database and included those with ≥1 claim for DA or levodopa between 09/01/2012 and 12/31/2018, ≥2 PD diagnoses, commercial or Medicare Advantage Part D (MAPD) insurance, ≥40 years old, and continuous medical and pharmacy coverage ≥12 months before and after index date. A subset of patients receiving DA monotherapy was selected for this analysis. Variables were analyzed descriptively. Adherence was measured with medication possession ratio (MPR) and proportion of days covered (PDC); defined as ≥0.80. Results: Patients (N = 642) had mean (SD) age of 70.2 (9.9) years, 70.6 % had MAPD coverage, and 61.7 % were male. Neurologists prescribed 64.6 % of DA monotherapy, and 56.9 % of patients had ≥2 PD diagnoses before or on the index date. Index therapy was discontinued by 44.1 % of patients, and 55.9 % persisted for 12 months without change. Mean (SD) time to discontinuation was 102 (79) days. Mean (SD) MPR for patients (n = 562) with ≥2 fills was 0.84 (0.2); 70.3 % were MPR adherent. Mean (SD) PDC for all 642 patients was 0.66 (0.3); 50.5 % were PDC adherent. Conclusion: Adherence and continuation of therapy were suboptimal, which could translate into poor patient outcomes. Future studies could provide insights on the impact of low adherence and persistence with DA monotherapy.